Bilateral Elastofibroma Dorsi as Differential Diagnosis in Posterior Chest Wall Tumor: A Case Report - Hansen, Frederik Lundgaard; Nørlinger, Thomas Stokholm; Thorninger, Rikke (Archives of Clinical and Medical Case Reports, 2020)
Elastofibroma dorsi (ED) is a relatively common, albeit rarely diagnosed, benign soft tissue tumor, often with a sub- or infrascapular localization. ED is most common in females >50 years of age, and is unilateral in 67-90% of cases [1]. The pathogenesis is unclear, but it is hypothesized that repeated microtrauma stemming from friction between the scapula and the posterior thoracic wall induces an abnormal proliferation of fibroelastic tissue. Studies have also shown considerable heritability [2]. The condition is often asymptomatic, but can result in pain and decrease in upper extremity function. The diagnosis is made from MRI or pathology examination of a biopsy or tissue post excision. The present paper discusses a case of bilateral ED in a 76 year old female with a history of several years of manual labor as a hairdresser.